Conceptualization of Strategic Information Systems Planning (SISP) success model in public sector: an absorptive capacity approach - Abu Bakar, Fazidah; Suhaimi, Mohd Adam; Hussin, Husnayati (2009)

(untitled)
The rapid changes in information technology (IT) and business environment have challenged the organizational capabilities in planning the appropriate information systems/information technology (IS/IT) strategies for organizations. With SISP consistently remains as one of the top managerial concerns, there is a need to find ways to improve SISP. Based on this scenario, the role of knowledge and knowledge based processes should be the central focus in SISP. Therefore, some studies have suggested that SISP process should be viewed as a learning process rather than a problem solving process. As a learning process, SISP success can be determined by how much impact the SISP practice has influenced on information system (IS) planners’ thinking and actions. In this case, knowledge capacity absorbed from SISP experience reflects a certain level of organizational learning (OL) or capability is achieved which later influences the SISP success. However, SISP study from this perspective is lacking. Synthesizing from the literature, this paper proposes a conceptual framework based on absorptive capacity model for an SISP success model in the public sector.